The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1590/s0034-71082000000100005
|View full text |Cite
|
Sign up to set email alerts
|

Foraging behavior of bee pollinators on the tropical weed Triumfetta semitriloba: flight distance and directionality

Abstract: We studied flight distance and directionality of bee pollinators on the tropical shrub weed Triumfetta semitriloba Jacq. (Tiliaceae), addressing (1) within-and between-plant movement pattern; (2) distances flown between plants; (3) flight directionality. Flowering plants were distributed in well-delimited clumps, in each of two pasture areas (A1 and A2) and one area of forest gap (A3), in Viçosa, southeastern Brazil. Five solitary bee species, Augochlorella michaelis, Augochloropsis cupreola, Pseudocentron pau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 23 publications
1
16
0
3
Order By: Relevance
“…This is consistent with a previous study of this fig (Moore et al, 2003b). Similar 'nearest neighbour' approaches to floral visitation have also been seen in unrelated pollinating insects including five solitary bee and two social bee species (Collevatti et al, 2000). (Ramirez, 1970;Janzen, 1979).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with a previous study of this fig (Moore et al, 2003b). Similar 'nearest neighbour' approaches to floral visitation have also been seen in unrelated pollinating insects including five solitary bee and two social bee species (Collevatti et al, 2000). (Ramirez, 1970;Janzen, 1979).…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed that after re-emerging, K. tentacularis foundresses (that are then wingless) could re-enter and oviposit in up to four further receptive figs and that they tended to enter the first receptive figs they encountered. Similar 'nearest neighbour' approaches to floral visitation have also been seen in unrelated pollinating insects including five solitary bee and two social bee species (Collevatti et al, 2000). Similar 'nearest neighbour' approaches to floral visitation have also been seen in unrelated pollinating insects including five solitary bee and two social bee species (Collevatti et al, 2000).…”
Section: Discussionmentioning
confidence: 61%
“…Os principais visitantes florais de Eugenia uniflora, E. neonitida, E. punicifolia e E. rotundifolia, que são abelhas de pequeno porte e moscas, apresentam uma amplitude forrageira baixa, comportamento que pode vir a diminuir o fluxo gênico entre as populações vegetais, diferentemente do que acontece com grandes polinizadores, como abelhas de grande porte, pássaros e mamíferos que podem carregar o pólen por longas distâncias (Collevatti et al 2000;Latouche-Hallé et al 2004).…”
Section: Resultsunclassified
“…Such pattern of variation could, in principle, favour generalization to all phenotypes by pollinators and prevent populations from maintaining their differences owing to increased gene flow. However, insect pollinators only perceive colours at relatively small spatial distances (Giurfa et al 1996;Dyer et al 2008) and move mostly between neighbouring plants (Waser 1982;Collevatti et al 2000;Saleh and Chittka 2007), which implies that they perceive colour variation only at a very local scale. Therefore, there may be discontinuous transitions at spatial scales that are biologically meaningful for pollinators even if flower colour variation seems continuous when considering all the plants of the hybrid zone together.…”
Section: Introductionmentioning
confidence: 99%